2018
DOI: 10.1007/s13187-018-1400-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Health Literacy, Cancer Prevention Beliefs, and Cancer Prevention Behaviors

Abstract: While cancer prevention behaviors have been clearly defined, many people do not engage in these risk-reduction behaviors. Factors such as cancer prevention beliefs and limited health literacy may undermine cancer prevention behavior recommendations. This study explored the relationships between cancer prevention beliefs, health literacy, and cancer prevention behaviors. Data were analyzed from the 2013 Health Information National Trends Survey (n = 1675). Regression analyses for four cancer prevention belief (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 21 publications
3
41
1
Order By: Relevance
“…Consistent with prior studies, participants with lower levels of education were less likely to report use of the internet to communicate with healthcare providers, search for health-related information, and use of social media or online blogs/support groups [ 24 , 54 ]. A potential mechanism explaining the association between education and internet use is the role of health and numeric literacy, which has been well documented in previous studies [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Lower levels of household income were also associated with lower likelihood of internet use to communicate with healthcare providers and searching for health information for others.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with prior studies, participants with lower levels of education were less likely to report use of the internet to communicate with healthcare providers, search for health-related information, and use of social media or online blogs/support groups [ 24 , 54 ]. A potential mechanism explaining the association between education and internet use is the role of health and numeric literacy, which has been well documented in previous studies [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Lower levels of household income were also associated with lower likelihood of internet use to communicate with healthcare providers and searching for health information for others.…”
Section: Discussionmentioning
confidence: 87%
“…9). Individuals who hold such fatalistic beliefs are more likely to have lower levels of engagement in preventive behaviors and have greater preference for avoidance of cancer risk information (9,17,21). Moreover, a cancer diagnosis is frequently linked with belief in inevitable death ("when I think about cancer, I automatically think about death") and this can create barriers to healthcareseeking behaviors as individuals with low self-efficacy attempt to delay confronting such threats (22).…”
Section: Introductionmentioning
confidence: 99%
“…In the health literacy concept model, as well as access, perception and use of cancer information also differ with health literacy level (Best et al, 2018; Shim, Kelly & Hornik, 2006; Smith, Trevena, Nutbeam, Barratt, & McCaffery, 2008). A study from the U.S. using Health Information National Trends data found that people with low health literacy were more likely to hold fatalistic cancer prevention beliefs (Fleary, Paasche-Orlow, Joseph, & Freund, 2018). This in turn could inhibit men with inadequate health literacy from seeking or acquiring any cancer information; however, more research is required.…”
Section: Discussionmentioning
confidence: 99%